Joint ventures in family and non-family firms - Gavana, Giovanna; Gottardo, Pietro; Moisello, Anna Maria (<center>Conference Proceedings Determinants Of Regional Development</center>; No 2 (2021): Conference Proceedings - VIII International Scientific Conference Determinants of Regional Development, 2021)
This paper aims to investigate how the nature of a company's ownership and board characteristics influence the investment choices in joint ventures from the dimensional point of view. In doing so, it analyzes an international sample of companies belonging to the major economies of continental Europe, controlling for the effect of the other intellectual capital components and for the fixed effects of industry, company and year. The results indicate that the type of joint venture, link vs scale, has a significant effect and, in particular, the choice of a link joint venture significantly reduces the size of the investment for family companies, whilst human capital efficiency increases JVs investment size for all firms. On the other hand, in relation to the nature of ownership, the presence of CEO duality has an opposite effect on the size of the investment in joint ventures, as it has a lowering effect in family businesses, while it exerts an amplifier influence in non-family businesses.